A Numerical Study on the State of the Blast Furnace Thermal Reserve Zone under Different Starting Temperatures of Coke Solution Loss Reaction. Issue 7 (7th March 2022) - Meng, Fanchao; Shao, Lei; Ni, Wenjie; Zou, Zongshu
Abstract : As a measure to improve the blast furnace gas utilization efficiency during the iron making, decreasing the temperature of blast furnace thermal reserve zone (here called TRZ for short) by increasing the coke reactivity and therefore lowering the starting temperature of coke solution loss reaction (CSLR) has received much attention. However, this measure is proposed merely from a thermodynamic point of view by considering that the FeO reduction with CO is slightly exothermic. The effect of the CSLR starting temperature on the state of TRZ that also determines the kinetic conditions for indirect reduction has yet to be clarified. For this, a 1D kinetic model built previously is adopted in this paper to investigate how the TRZ state and gas utilization efficiency respond to the changes in the starting temperature of CSLR. The results show that with a decrease in the starting temperature, the height and average temperature of TRZ decrease, and the lower edge of TRZ shifts upwards. The gas utilization efficiency increases first and then decreases, thus leading to a critical starting temperature. Moreover, a lower critical temperature corresponds to a higher gas utilization efficiency. An increase in iron ore reducibility or top pressure can lower the critical temperature. Abstract : The effect of the coke solution loss reaction starting temperature on the state of blast furnace thermal reserve zone that also determines the kinetic conditions for indirect reduction is investigated using a mathematical model in which the countercurrent reactive flow of reducing gas and iron bearing ore is taken into account.